TINJAUAN FIQIH MUAMALAH TERHADAP PERBEDAAN HARGA PUPUK BERSUBSIDI ANTARA KOPERASI DAN DISTRIBUTOR DI DESA KANCA KECAMATAN PARADO KABUPATEN BIMA - Muhammad; Imron Hadi (Universitas Islam Negeri Mataram, 2021)
The supply of fertilizer from the government, especially in Kanca Village, Parado District, Bima Regency, is very minimal, so that the price of fertilizer from the Cooperative and Distributors has a different price from the standard price. As a result, many of them complain about this, while the need for fertilizer for farmers in Kanca Village, Parado District, Bima Regency is quite high, because the potential for agricultural land, both rice fields and irrigated or rain-fed fields, is quite extensive. Considering the need for fertilizer, distribution from producers to consumers plays an important role in meeting the fertilizer needs of farmers.